2010
DOI: 10.3201/eid1602.091032
|View full text |Cite
|
Sign up to set email alerts
|

Associations betweenMycobacterium tuberculosisStrains and Phenotypes

Abstract: This population-based study was used to investigate strong associations between phenotypes and genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 35 publications
7
39
1
Order By: Relevance
“…Additional data from other groups also indicate that RD Rio could be associated with drug resistance. Gavín et al described MDR strains of M. tuberculosis RD Rio sublineage (LAM9 subfamily) in Spain from Equatorial Guinean patients (39), and Brown et al showed that LAM1 (a marker for RD Rio ) was associated with resistance to both pyrazinamide and streptomycin in MTB cases from London, United Kingdom (33), while the study performed in New York, NY, demonstrated that RD Rio was associated with resistance to isoniazid (24). Although this is a matter of speculation, it is interesting that a strain from LAM4, a subfamily that contains both WT and RD Rio strains, is the major cause of XDR-TB in South Africa (17) and that both LAM9 (predominantly RD Rio but also containing WT) and LAM1 (exclusively RD Rio ) subfamilies were major contributors to drug resistance in Russia (14,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional data from other groups also indicate that RD Rio could be associated with drug resistance. Gavín et al described MDR strains of M. tuberculosis RD Rio sublineage (LAM9 subfamily) in Spain from Equatorial Guinean patients (39), and Brown et al showed that LAM1 (a marker for RD Rio ) was associated with resistance to both pyrazinamide and streptomycin in MTB cases from London, United Kingdom (33), while the study performed in New York, NY, demonstrated that RD Rio was associated with resistance to isoniazid (24). Although this is a matter of speculation, it is interesting that a strain from LAM4, a subfamily that contains both WT and RD Rio strains, is the major cause of XDR-TB in South Africa (17) and that both LAM9 (predominantly RD Rio but also containing WT) and LAM1 (exclusively RD Rio ) subfamilies were major contributors to drug resistance in Russia (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…As examples, we mention strains within the W/Beijing spoligotype that produce a modified phenoglycolipid associated with an insertion in the pks15/1 gene and dampened induction of interleukin-6 (IL-6), IL-12, and tumor necrosis factor (TNF) (30,31) and the CDC1551 strain that is associated with inducing a higher proinflammatory response (32). One of the mechanisms of Mycobacterium that could underlie the evasion from the host immune response is alteration of expression of the genes belonging to the PPE/PE_PGRS family, encoding surface proteins associated with mycobacterial virulence and host immune response (1,33,34). We previously speculated that in M. tuberculosis strains with the RD Rio deletion, the loss of two PPE genes (PPE55 and PPE56) could minimize host immune recognition, leading to enhanced virulence and/or transmissibility (21).…”
Section: Discussionmentioning
confidence: 99%
“…Over 10 years, this strain grew from causing a few cases, to dominate the country's M. tuberculosis population (Kruuner et al 2001). Brown et al (2010) have demonstrated that global MTBC diversity is reflected in strains circulating in London. Based on VNTR typing, 23 London isolates were selected to represent maximum variability across the entire MTBC and particularly within the Beijing lineage.…”
Section: Selection Of Mtbc Isolates For Genome Sequencingmentioning
confidence: 99%
“…The application of molecular approaches for detecting variation among Mycobacterium tuberculosis isolates has generated new appreciation for the diversity present within this relatively genetically conserved bacterial species (4,17). Genotyping methods, such as insertion sequence typing (IS6110), spacer oligonucleotide typing (spoligotyping), and mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) typing, have been used to identify transmission chains (1,10,18,26), to classify strains into families and lineages (2,5,9,18,27,29), to identify episodes of exogenous reinfection (3,20,25,31), and, most recently, to detect the presence of within-host genetic heterogeneity (11,19,24,33).…”
mentioning
confidence: 99%